Pengaruh Budaya Sekolah Dan Hubungan Interpersonal Antar Siswa Terhadap Motivasi Belajar Siswa Kelas XI Program Keahlian Akuntansi Di SMK N 1 Klaten Tahun pelajaran 2015/1016 - Budiyatun, Desmi, Dr. Sabar Narimo, MM, M.Pd (2016)
The purpose of this study are: to determine 1) the effect of school culture on motivation to learn accounting class XI student of SMK N 1 Klaten in the academic year 2015/2016. 2) the effect of interpersonal relationships between students' motivation to learn accounting class XI student of SMK N 1 Klaten in the academic year 2015/2016. 3) the effect of school culture and interpersonal relationships between students' motivation to learn accounting class XI student of SMK N 1 Klaten in the academic year 2015/2016. This study uses quantitative methods associative. The population in this study were all students of class XI accounting SMK N 1 Klaten in the academic year 2015/2016. The sampling technique used Porporsional Sample random sampling that as many as 105 respondents. Necessary data obtained through questionnaires and documentation. The questionnaire has previously been tested and tested for validity and reliability were tested. Data analysis technique used is the prerequisite analysis using normality test and linearity test, whereas hypothesis testing using multiple linear regression, F test, t-test, R2, and the relative contribution and effective. The results of the regression equation obtained regression equation motivation to learn that Y = 11.307 + 0,413X1 + 0,442X2. The conclusion of this study were: 1) School culture significantly influence student motivation. This is evident from the test results were obtained thitung t> t table (5,999> 1,983); 2) interpersonal relationships between students significantly influence student motivation. This is evident from the test results were obtained thitung t> t table (6.292> 1.983); 3) School culture and interpersonal relationships between students jointly significant effect on students' motivation. This is evident from the test results were obtained Fhitung F> F table (58.978> 3.085). Test results obtained by the value of the coefficient of determination R2 = 0.536, meaning that 53.6% mean change / variation Y (Motivation) caused by the change / variation of the variable X (Culture Interpersonal Relationships Between Schools and Students), while 46.4% were due to to changes in other variables not included in other models and so on.